Inherited Thrombophilia in Pediatric Venous Thromboembolic Disease: Why and Who to Test - van Ommen, C. Heleen; Nowak-Göttl, Ulrike (Frontiers in Pediatrics, 2017)
Venous thromboembolic disease in childhood is a multifactorial disease. Risk factors include acquired clinical risk factors such as a central venous catheter and underlying disease, and inherited thrombophilia. Inherited thrombophilia is defined as a genetically determined tendency to develop venous thromboembolism. In contrast to adults, acquired clinical risk factors play a larger role than inherited thrombophilia in the development of thrombotic disease in children. The contributing role of inherited thrombophilia is not clear in many pediatric thrombotic events, especially catheter-related thrombosis. Furthermore, identification of inherited thrombophilia will not often influence acute management of the thrombotic event as well as the duration of anticoagulation. In some patients, however, detection of inherited thrombophilia may lead to identification of other family members who can be counseled for their thrombotic risk. This article discusses the potential arguments for testing of inherited thrombophilia, including factor V Leiden mutation, prothrombin mutation, and deficiencies of antithrombin, protein C, or protein S, and suggests some patient groups in childhood, that may be tested.